Aspects Therapeutic of Disorder of Attention Deficit Hyperactivity Disorder - Ferreira, Samuell Santos; Moura Campos Zeron, Rubens; da Silva Santos, Tatiane; Damasceno Ribeiro, Patrícia; Garcia Silva, Juliana; Campos de Albuquerque, Victor (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2019)
The aim of this study was to demonstrate the importance of early diagnosis and the contribution of multidisciplinary therapeutic procedures to alleviate the symptoms of individuals with ADHD. Treatment should be multidisciplinary, involving various professionals with the family. We conclude that pharmacological treatment is quite effective, although in some individuals with the disorder, pharmacological treatment is not enough because the symptoms persist or there is comorbidity. Therefore, it is essential for early diagnosis of ADHD with correct implementation of treatment for better prognosis.